2018
DOI: 10.3892/ol.2018.8170
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 1 expression is associated with response to adjuvant chemotherapy in stage�II and III colorectal cancer

Abstract: Aquaporin 1 (AQP1), which functions as a water transporter, is associated with cancer cell proliferation, invasion, metastasis and angiogenesis in numerous types of solid cancer, including colorectal cancer (CRC). The focus of the present study was to address the potential clinical use of AQP1 expression in CRC as a prognostic and predictive biomarker for disease recurrence and therapeutic outcomes. The current study investigated the expression of AQP1 in surgically resected specimens from 268 patients with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
(53 reference statements)
0
17
0
Order By: Relevance
“…Yoshida et al reported expression in 56 of 120 (46.7%) patients with stage II and III colon cancer [8]. Imaizumi et al reported expression in 112 of 268 (41.8%) patients with stage 0-IV CRC [10]. In the largest study previously reported, Kang et al reported strong positive staining in 298 of 486 patients with stage I-III colon cancer (61.3%) [9].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Yoshida et al reported expression in 56 of 120 (46.7%) patients with stage II and III colon cancer [8]. Imaizumi et al reported expression in 112 of 268 (41.8%) patients with stage 0-IV CRC [10]. In the largest study previously reported, Kang et al reported strong positive staining in 298 of 486 patients with stage I-III colon cancer (61.3%) [9].…”
Section: Discussionmentioning
confidence: 98%
“…There are limited published data comparing AQP1 expression in normal colonic mucosa to CRC. Imaizumi et al reported that AQP1 protein was not detected in the normal epithelial cells but was expressed in 112 of 268 (41.8%) of stage 0 to IV CRC [10]. Mobasheri et al evaluated the relative abundance and distribution of AQP1 protein using immunohistochemistry and quantitative histomorphometric analysis of tissue microarrays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It's worth noting that most studies show that AQP1 gene acts as an oncogene in various solid cancers to promote cancer development (12)(13)(14), whereas only a few studies report AQP1 as a tumor suppressor that inhibits tumor growth (21,58). Recently, Marietta Tan et al also showed that AQP1 was epigenetically downregulated by promoter methylation and was associated with improved prognosis in salivary gland adenoid cystic carcinoma (20).…”
Section: Discussionmentioning
confidence: 99%
“…facilitates transcellular water transportation (11). AQP1 plays an oncogenic role in many types of solid cancer, including colorectal cancer, breast cancer, bladder cancer (12)(13)(14). Functionally, AQP1 regulates cell proliferation, invasion, metastasis and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%